2007
DOI: 10.1093/intimm/dxm017
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/AKT/mTOR hypersignaling in autoimmune lymphoproliferative disease engendered by the epistatic interplay of Sle1b and FASlpr

Abstract: Previous studies have demonstrated that the NZM2410/NZW 'z' allele of Sle1 on telomeric murine chromosome 1 led to lymphoproliferative autoimmunity, when acting in concert with the FAS(lpr) defect on the C57BL/6 background. The present report shows that the Sle1b sub-locus, harboring the NZM2410/NZW 'z' allele of SLAM, in epistasis with FAS(lpr), may be sufficient to induce lymphoproliferative autoimmunity. Disease in this simplified genetic model is accompanied by significant activation of the AKT signaling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…S6 is phosphorylated downstream of the AKT/mTOR pathway and integrates multiple signals, including those of the MAPK pathway (13,14). Sustained activation of T cells, regardless of the initiating trigger, is associated with S6 kinase activity (34)(35)(36). The higher phosphorylation state of S6 in clone 2E2 is in accord with these data.…”
Section: Discussionsupporting
confidence: 53%
“…S6 is phosphorylated downstream of the AKT/mTOR pathway and integrates multiple signals, including those of the MAPK pathway (13,14). Sustained activation of T cells, regardless of the initiating trigger, is associated with S6 kinase activity (34)(35)(36). The higher phosphorylation state of S6 in clone 2E2 is in accord with these data.…”
Section: Discussionsupporting
confidence: 53%
“…The molecular mechanisms responsible for the mTOR‐dependent activation of NOX and NF‐κB in response to BCAA are unknown and this is a limitation of our study. However, other authors have also found a role for mTOR in oxidative stress generation40, 41 or NF‐κB activation in response to different stimuli or pathological conditions 42, 43. Besides mTORC1, BCAA trigger several signalling responses via the activation of AMPK, which plays a role in cellular energy homoeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…These studies strongly suggest that members of the NF-kB/Rel family perform nonoverlapping functions, and that loss-of-function mutations of NF-kB/Rel genes cannot be fully compensated by other members of same family. Recent evidence suggests that perturbed signals (the M55V substitution in SUMO4 [45], PI3K-AKT hypersignaling [46], increased TNF-a [47]) all lead to the elevated activation of NF-kB and have been associated with lymphoproliferative or autoimmune diseases. Since constitutive expression of Foxp3 is essential for Treg function, and the function of NF-kB is also attenuated by physical interaction with Foxp3 [48], it would be interesting to investigate the role of NF-kB isoforms in the expression of Foxp3.…”
Section: Tgf-b1 Attenuates Nf-jb Binding On Foxp3 Promotermentioning
confidence: 99%